Autoritarismo, repressão e propaganda: a Paraíba no governo Argemiro de Figueiredo (1937-1940) - Silva, Waniéry Loyvia de Almeida (2017)
This research aims at analyzing the administration and actions of the intervener Argemiro de Figueiredo (1937-1940), regarding the framing of Paraíba the ideology imposed by the Estado Novo, the reflexes of authoritarianism within the State, the continuity of the practices of Mandonismo and Clientelismo typical of the coronelistico system and the actions of repression and fight against communism. It is also in our interest to notice how over the years, endowed with a great advertising machine, the interventor associated with the media, the Catholic Church and the various oligarchical factions, managed to "make" a positive image of the collective imagination , Emerging as one of the most respected politicians of the Paraíba historiography. In this process, the school and other educational institutions appear as indispensable to the argemirista political project, since they functioned as spaces of indoctrination. Throughout the dissertation we try to demonstrate the political trajectory of Argemiro de Figueiredo, in order to understand how it was possible to ascend to the Executive Power from 1935, and the construction of Argemirismo, that allowed the interventor to appease the intra-oligarchic conflicts, becoming Thus a hegemonic leadership within the state. To develop this research we anchor ourselves in the contributions provided by the renovation through which Political History passed, thus appropriating the concept of Political Culture. With regard to the sources used, we seek to establish a dialogue with authors who already refer to this topic, and sources such as newspapers, official documents and letters.